Cost-effectiveness analysis of the early transition from microscopic to biportal endoscopic unilateral laminectomy bilateral decompression - Sung-Eun Kwon; Hangeul Park; Noah Hong; Woojin Kim; Jungbo Sim; Ho Sung Myeong; Seunghoon Lee; Jun-Hoe Kim; Chang-Hyun Lee; Fon-Yih Tsuang; Chi Heon Kim (Medicine, 2026)
This study aimed to compare the clinical outcomes and cost-effectiveness of microscopic unilateral laminectomy bilateral decompression (ULBD) and biportal endoscopic ULBD during the early transition phase from microscopic to endoscopic surgery for lumbar spinal stenosis. We retrospectively reviewed patients who underwent single-level lumbar ULBD between January 2017 and December 2023 at a single tertiary center. Clinical outcomes included Numeric Rating Scale (NRS) for back and leg pain, Oswestry Disability Index, and Euro Quality of Life-5 Dimension index values. Primary and secondary costs were assessed, quality-adjusted life year (QALY) was calculated, and incremental cost-effectiveness ratio was estimated with bootstrap analysis. Cost-effectiveness was compared at 12 months postoperatively. A total of 69 patients were included (39 microscopic ULBD and 30 endoscopic ULBD). Both groups showed postoperative improvement in Numeric Rating Scale, Oswestry Disability Index, and Euro Quality of Life-5 Dimension at 12 months compared with baseline, with no statistically significant differences between groups. Total costs and QALY gain at 12 months did not differ significantly between the groups. The observed incremental cost-effectiveness ratio was −$2816.36/QALY. Exploratory bootstrap and cost-effectiveness acceptability curve analyses showed a favorable numerical direction for endoscopic ULBD; however, these findings were interpreted as descriptive estimates of uncertainty rather than evidence of economic superiority. In this early transition phase, endoscopic ULBD demonstrated comparable 12-month clinical and economic outcomes relative to microscopic ULBD. The exploratory cost-effectiveness findings should be interpreted cautiously and should not be considered evidence of economic superiority. Further large-scale, prospective studies with concurrent comparison groups and longer follow-up are warranted.